Prognostic significance of TIMP-1 in non-small cell lung cancer - Pesta, Martin; Kulda, Vlastimil; Kucera, Radek; Pesek, Milos; Vrzalova, Jindra; Liska, Vaclav; Pecen, Ladislav; Treska, Vladislav; Safranek, Jarmil; Prazakova, Marketa; Vycital, Ondrej; Bruha, Jan; et al. (Anticancer research, 2011)
UNLABELLED: Tissue inhibitor of metalloproteinases 1 (TIMP1) regulates not only extracellular matrix catabolism but the major effect in tumor tissue is promotion of cell growth and anti-apoptotic activity. The aim of our study was to evaluate plasma TIMP1 levels and tissue TIMP1 mRNA expression as prognostic markers in NSCLC patients. PATIENTS AND METHODS: We studied a group of 108 patients with NSCLC who had undergone lung surgery. Estimation of TIMP1 mRNA was performed by quantitative polymerase chain reaction (qPCR) and estimation of plasma TIMP1 protein using enzyme-linked immunosorbent assay (ELISA). RESULTS: There was shorter disease-free interval (DFI) for NSCLC patients at stage II, with a higher expression of TIMP1 mRNA in tumor tissue (p=0.0246). We recorded a relationship between tumor tissue TIMP1 mRNA expression and DFI in squamous cell carcinoma (SCC) (p=0.0117). Shorter overall survival was found in patients at stages IIIa+IIIb+IV, with a higher expression of TIMP1 mRNA (p=0.0389). We found differences in plasma TIMP1 levels between patients with SCC and those with adenocarcinoma (p=0.0491). CONCLUSION: A higher tissue level of TIMP1 mRNA is related to an adverse prognosis of patients. However, our results did not show any relation of TIMP1 protein in blood plasma to prognosis.
Keywords: senioři; messenger RNA; spinocelulární karcinom; Prognosis; Middle Aged; mužské pohlaví; nádory plic; adenokarcinom; míra přežití; Adult; Biomarkers, Tumor; polymerázová řetězová reakce s reverzní transkripcí; Neoplasm Staging; nemalobuněčný karcinom plic; nádorové biomarkery; ELISA; ženské pohlaví; prognóza; tkáňový inhibitor metaloproteinasy 1; Humans; RNA, Messenger; Survival Rate; Lung Neoplasms; Carcinoma, Non-Small-Cell Lung; lidé středního věku; staging nádorů; Reverse Transcriptase Polymerase Chain Reaction; Enzyme-Linked Immunosorbent Assay; dospělí; Tissue Inhibitor of Metalloproteinase-1; Carcinoma, Squamous Cell; Female; Aged; Adenocarcinoma; lidé; Male